PELANGGARAN MEREK DAGANG DALAM KASUS PERSAMAAN NAMA MEREK PADA GEPREK BENSU MENURUT UNDANG UNDANG UU NO. 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS - Aspriola, Vieri Aspriola; Chairunisa Israd, Agri (Journal Evidence Of Law, 2022)
Knowing the legal protection for registered marks and analyzing the Court Decision Number 57 / Pdt.Sus-Merek / 2019 / Pn Niaga Jkt-Pst are the purposes of this research paper. In this research paper uses a case approach with a normative juridical method. Examining library materials is a source of data from normative juridical research. The results showed that there was legal protection for trademark owners who were legally registered. Based on the procedures and laws in force, Geprek Bensu should not be able to be registered because the registration of its trademark copyright was carried out in bad faith. This is because Geprek Bensu has a fundamental and or complete similarity with the I am Geprek Bensu brand and the name of the legal entity PT. Chicken Geprek Benny Sujono. In addition, I Am Geprek Bensu has obtained legal protection for its trademark rights because it has been registered beforehand. This legal protection is obtained because in Indonesia it applies a first to file system.